Effect of a flow-streamlining implant at the distal anastomosis of a coronary artery bypass graft - Pedroso, Pedro D.; Eleftheriou, Evangelos C.; Anayiotos, Andreas (My University, 2002)
Intimal thickening in the coronary artery bypass graft (CABG) distal anastomosis has been implicated as the, major cause of restenosis and long-term graft failure. Several studies point to the interplay between nonumiform hemodynamics including disturbed flows and recirculation zones, wall shear stress, and long particle residence time as possible etiologies. The hemodynamic features of two anatomic models of saphenous-vein CABGs were studied and compared. One simulated an anastomosis with both diameter and compliance mismatch and a curvature at the connection, analogous to the geometry observed in a conventional cardiothoracic procedure. The other, simulated an anastomosis with a flow stabilizing anastomotic implant connector which improves current cardiothoracic procedures by eliminating the distal vein bulging and curvature. Physiologic flow conditions were imposed on both models and qualitative analysis of the flow was performed with dye injection and a digital camera. Quantitative analysis was performed with laser Doppler velocimetry. Results showed that the presence of the bulge at the veno-arterial junction, contributed to the formation of accentuated secondary structures (helices), which progress into the flow divider and significantly affect radial velocity components at the host vessel up to four diameters downstream of the junction. The model with the implant, achieved more hemodynamically efficient conditions on the host vessel with higher mean and maximum axial velocities and lower radial velocities than the conventional model. The presence of the sinus may also affect the magnitude and shape of the shear stress at locations where intimal thickening occurs. Thus, the presence of the implant creates a more streamlined environment with more primary and less secondary flow components which may then inhibit the development of intimal thickening, restenosis, and ultimate failure of the saphenous vein graft.
Keywords: Cameras; Computer simulation; Fetal heart rate monitoring; Arteriovenous anastomosis